Cardiovascular magnetic resonance characterisation of anthracycline cardiotoxicity in adults with normal left ventricular ejection fraction. (15th November 2021) - Harries, Iwan; Berlot, Bostjan; ffrench-Constant, Natasha; Williams, Matthew; Liang, Kate; De Garate, Estefania; Baritussio, Anna; Biglino, Giovanni; Plana, Juan Carlos; Bucciarelli-Ducci, Chiara
Abstract: Background: Anthracycline therapy may lead to changes in cardiac structure and function not detectable by solely evaluating left ventricular ejection fraction (LVEF). Objectives: We hypothesized that cardiovascular magnetic resonance (CMR) would identify structural and functional myocardial abnormalities in anthracycline-treated cancer survivors with normal LVEF, compared to a matched control population. Methods: Forty-five cancer survivors (56 ± 16 yrs., 60% female) with normal LVEF (59.5 ± 4.1%) were studied a median of 11 months (range 3–36) following administration of 237 ± 83 mg/m 2 anthracycline, and compared with forty-five healthy control subjects of similar age and sex (53 ± 16 yrs., 60% female) with normal LVEF (60.8 ± 2.4%) using 1.5 T CMR. Results: Significantly smaller indexed left ventricular mass (45.6 ± 8.7 vs 50.3 ± 10.1 g/m 2, p = 0.02) and indexed myocardial cell volume (30.5 ± 5.7 vs 34.8 ± 7.2 ml/m 2, p = 0.002) were evident in cancer survivors and the latter was inversely associated with cumulative anthracycline dose ( r = −0.31, p = 0.02). Surrogate CMR markers of myocardial fibrosis were significantly increased in cancer survivors (native myocardial T1 : 1021 ± 40 vs 996 ± 35 ms, p = 0.002; extracellular volume: 29.5 ± 4.5 vs 27.4 ± 2.3%, p = 0.006). CMR-derived feature-tracking global longitudinal strain (GLS) was significantly impaired in cancer survivors (2D GLS -18.3 ± 2.6 vs −20.0 ± 2.0%, p < 0.001; 3D GLS -14.5 ± 2.3 vs −16.4 ± 2.6%, p < 0.001). Parameters exhibited good to excellent (ICC = 0.86–0.98) inter- and intra-observer reproducibility. Conclusions: Anthracycline-treated cancer survivors with normal LVEF have significant perturbations of LV mass, myocardial cell volume, native myocardial T1, ECV, CMR-derived 2D and 3D GLS, compared to controls, with good to excellent levels of inter- and intra-observer reproducibility. Highlights: Compared to a control population, anthracycline treated cancer survivors with normal LVEF have: Significantly impaired CMR-derived GLS (2D and 3D). Significantly elevated native myocardial T1 and ECV. Significantly reduced indexed LV mass. Indexed myocardial cell volume is inversely associated with anthracycline dose.